Experiences and Practices in GUI Functional Testing: A Software Practitioners’ View - Junior, Nailton; Costa, Heitor; Karita, Leila; Machado, Ivan; Soares, Larissa (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
Software testing is an important activity to ensure software quality. A widely performed type of testing is GUI (Graphical User Interface) functional testing, where the aim is to evaluate the software functionality through their graphic interface. We can find in the literature techniques and solutions for handling GUI functional testing in the last years. However, studies that deeply analyze how professionals in the industry perform GUI functional testing are still lacking. In this study, we investigated how testing professionals perform GUI functional testing. We surveyed 222 professionals from different positions and roles who perform those tests. The results indicate that many professionals perform GUI functional testing without proper tool support. They also pointed out that GUI test automation tools have limitations. This study presents preliminary results to understand the Brazilian companies’ scenario on the difficulties of GUI functional testing.